Implementasi Peraturan Menteri Dalam Negeri Nomor 70 Tahun 2019 Tentang Sistem Informasi Pemerintahan Daerah pada Penerapan E-Planning dalam Perencanaan Pembangunan di Kabupaten Pakpak Bharat - Sumihar Lenniwaty Lumbantobing; Heri Kusmanto; Bengkel Ginting (Universitas Medan Area, 2022)
This study aims to determine and analyze the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning the Regional Government Information System (SIPD) on the implementation of e-planning in development planning in the Pakpak Bharat Regency. The research approach is descriptive qualitative which data collection is done by interview, observation, and documentation study. The study conducted an analysis using Edward III's theory by analyzing the factors of communication, resources, disposition, and organizational structure. The results showed that the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems (SIPD) on the implementation of e-planning in development planning in the Pakpak Bharat Regency went quite smoothly. The attitude and response of the implementers in carrying out the mandate of the SIPD policy are good and quite committed, as evidenced by their efforts and efforts to meet the deadlines of the planning schedule. However, there are still some obstacles, such as a lack of understanding of the classification, codification,n and nomenclature of development planning and regional finance, infrastructure constraints (network or server), the readiness of unit price standards (SSH), and the absence of SOPs. Improvement of the quality of human resources for planners must be carried out so that they can keep up with changes in dynamic information systems and the resulting planning documents are of higher quality.